Expression of integrin ανβ6 differentiates perihilar cholangiocarcinoma (PHC) from benign disease mimicking PHC. (March 2021) - Franken, L.C.; Vuijk, F.A.; Soer, E.C.; Roos, E.; Erdmann, J.I.; Hooijer, G.K.J.; Vahrmeijer, A.L.; Gambhir, S.S.; van Gulik, T.M.; Sarasqueta, A. Farina; Verheij, J.; Swijnenburg, R.J.
Abstract: Background: Approximately 15% of patients undergoing resection for presumed perihilar cholangiocarcinoma (PHC) have benign disease at final pathological assessment. Molecular imaging targeting tumor-specific biomarkers could serve as a novel diagnostic tool to reduce these futile surgeries. Imaging agents have been developed, selectively binding integrin αν β6, a cell receptor upregulated in pancreatobiliary malignancies, for both (preoperative) PET and (intraoperative) fluorescent imaging. Here, expression of integrin αν β6 is evaluated in PHC, intrahepatic cholangiocarcinoma (ICC), hepatocellular carcinoma (HCC) and benign disease mimicking PHC using immunohistochemistry. Materials & methods: Three tissue microarrays (TMA) including 103 PHC tumor cores and sixty tissue samples were selected from resection specimens of pathologically proven PHC (n = 20), ICC (n = 10), HCC (n = 10), metastatic PHC lymph nodes (n = 10) and benign disease (presumed PHC with benign disease at pathological assessment, n = 10). These samples were stained for integrin αν β6 and quantified using the H-score. Results: Immunohistochemical staining for integrin αν β6 showed membranous expression in all twenty PHC whole mount slides (100%) and 93 out of 103 (92%) PHC tumor cores. Mean H-score of PHC samples was 195 ± 71, compared to a mean H-score of 126 ± 57 in benign samples (p = 0.013). In both benign and PHC samples, inflammatory infiltrates and pre-existent peribiliary glands showed integrin αν β6 expression. The mean H-score across ten ICC was 33 ± 53, which was significantly lower compared to PHC (p < 0.001) but too weak to consistently discriminate ICC from HCC (H-score 0)(p = 0.062). Conclusion: Integrin αν β6 is abundantly expressed in PHC and associated metastatic lymph nodes. Expression is significantly higher in PHC as compared to benign disease mimicking PHC, ICC and HCC, emphasizing its potential as a target for tumor-specific molecular imaging.